The Rise of Refractory Transition‐Metal Nitride Films for Advanced Electronics and Plasmonics - Jiachang Bi; Ruyi Zhang; Xiong Yao; Yanwei Cao (Advanced Materials Interfaces, 2025)
Abstract The advancement of semiconductor materials has played a crucial role in the development of electronic and optical devices. However, scaling down semiconductor devices to the nanoscale has imposed limitations on device properties due to quantum effects. Hence, the search for successor materials has become a central focus in the fields of materials science and physics. Transition‐metal nitrides (TMNs) are extraordinary materials known for their outstanding stability, biocompatibility, and ability to integrate with semiconductors. Over the past few decades, TMNs have been extensively employed in various fields. However, the synthesis of single‐crystal TMNs has long been challenging, hindering the advancement of their high‐performance electronics and plasmonics. Fortunately, progress in film deposition techniques has enabled the successful epitaxial growth of high‐quality TMN films. In comparison to reported reviews, there is a scarcity of reviews on epitaxial TMN films from the perspective of materials physics and condensed matter physics, particularly at the atomic level. Therefore, this review aims to provide a brief summary of recent progress in epitaxial growth at atomic precision, emergent physical properties (superconductivity, magnetism, ferroelectricity, and plasmon), and advanced electronic and plasmonic devices associated with epitaxial TMN films.